Assessing Photoreceptor Structure in Retinitis Pigmentosa and Usher Syndrome - Sun, Lynn W.; Johnson, Ryan D.; Langlo, Christopher S.; Cooper, Robert F.; Razeen, Moataz M.; Russillo, Madia C.; Dubra, Alfredo; Connor, Thomas B.; Han, Dennis P.; Pennesi, Mark E.; Kay, Christine N.; Weinberg, David V.; et al. (Investigative ophthalmology & visual science, 2016)
The purpose of this study was to examine cone photoreceptor structure in retinitis pigmentosa (RP) and Usher syndrome using confocal and nonconfocal split-detector adaptive optics scanning light ophthalmoscopy (AOSLO). Nineteen subjects (11 RP, 8 Usher syndrome) underwent ophthalmic and genetic testing, spectral-domain optical coherence tomography (SD-OCT), and AOSLO imaging. Split-detector images obtained in 11 subjects (7 RP, 4 Usher syndrome) were used to assess remnant cone structure in areas of altered cone reflectivity on confocal AOSLO. Despite normal interdigitation zone and ellipsoid zone appearance on OCT, foveal and parafoveal cone densities derived from confocal AOSLO images were significantly lower in Usher syndrome compared with RP. This was due in large part to an increased prevalence of non-waveguiding cones in the Usher syndrome retina. Although significantly correlated to best-corrected visual acuity and foveal sensitivity, cone density can decrease by nearly 38% before visual acuity becomes abnormal. Aberrantly waveguiding cones were noted within the transition zone of all eyes and corresponded to intact inner segment structures. These remnant cones decreased in density and increased in diameter across the transition zone and disappeared with external limiting membrane collapse. Foveal cone density can be decreased in RP and Usher syndrome before visible changes on OCT or a decline in visual function. Thus, AOSLO imaging may allow more sensitive monitoring of disease than current methods. However, confocal AOSLO is limited by dependence on cone waveguiding, whereas split-detector AOSLO offers unambiguous and quantifiable visualization of remnant cone inner segment structure. Confocal and split-detector thus offer complementary insights into retinal pathology.